RIWAYAT PAPARAN PESTISIDA SEBAGAI FAKTOR RISIKO STUNTING PADA ANAK USIA 2-5 TAHUN DI DAERAH PERTANIAN - Kusuma Yati Alim; Ali Rosidi; Suhartono Suhartono (GIZI INDONESIA, 2018)
The prevalence of stunting in the WanayasaSubdistrict area reached 23.7 percent and the stunting incidence was widely found in children aged 2-5 years. History of pesticide exposure is one of the factors that influence the incidence of stunting. WanayasaSubdistrict is an area of potato and vegetable farming with high intensity of pesticide use in processing the land.The purpose of study was to analyze the history of pesticide exposure as a risk factor for stunting in children aged 2-5 years in WanayasaSubdistrict,Banjarnegara District.The research design used was case control with a total sample of 47 cases (stunting) and 47 controls (not stunting). Subject selection by purposive sampling with matching age and gender. Data obtained through measurement of height, weight and structured interviews. Data were analyzed using chi-square test, calculating Odds Ratio (OR) and logistic regression method. The results showed that the lowest value ofHAZ in the case group were -5.4 SD and the highest was -2.55 SD, the lowest age of children 24-month in case group and 27-month in the control group. Most of mother’s work in case group (51.1%) and in control group (57.4%) were farmers. In multivariate analysis showed that, the history of pesticide exposure in children (OR = 4.21, 95% CI: 1.77-10.04) as stunting risk factor, and history of pesticide exposure during pregnancy was not significantly related to stunting. The conclusion of this study that the history of pesticide exposure is the most dominant risk factor for the incidence ofstuntingin children aged 2-5 years.